Content validation of the National Comprehensive Cancer Network/Functional Assessment of Cancer Therapy Lymphoma Symptom Index-18 (NFLymSI-18) in indolent B-cell non-Hodgkin's lymphoma - Courtney N. Hurt; Karen Kaiser; Sara Shaunfield; Kimberly A. Webster; Karen Keating; Lara Boyken; Sara Duffey; Jessica Garcia; David Cella (SpringerOpen, 2024)
Abstract Background The NFLymSI-18 is a patient-reported outcome measure comprised of the highest priority symptoms, emotional concerns, treatment side effects, and other concerns identified by lymphoma patients and oncologists. This study assessed the content validity of the NFLymSI-18 for patients with indolent B-cell non-Hodgkin's lymphoma (iNHL), with a focus on the Disease-Related Symptoms Physical (DRS-P) subscale. Methods Patients with a confirmed iNHL diagnosis who had received one or more lines of treatment were recruited during clinic visits. Patients described their symptoms, treatment side effects, and emotional concerns related to iNHL in a semi-structured interview. Qualitative data were analyzed using NVivo10. Results Data saturation was obtained by the 18th interview. Most participants (67%) had follicular lymphoma. 28% of participants had marginal zone lymphoma, and one participant had lymphoplasmacytoid lymphoma/Waldenström macroglobulinemia. Mean age of the 18 participants was 67 years. 56% of the sample was male. Most participants (67%) had a college or advanced degree. When asked to describe their iNHL symptoms, patients most often discussed swelling (n = 14), fatigue (n = 11), and pain (n = 8). The following symptoms were mentioned by three patients each: anxiety, appetite loss, rash, sleep disruption, trouble breathing, and malaise. Mapping of NFLymSI-18 content to these concerns showed the instrument includes all those most frequently mentioned symptoms. Conclusions This study supports the content validity of the NFLymSI-18, including its DRS-P Subscale, for patients with iNHL. The instrument shows strong validity for the most referenced symptoms of swelling, fatigue, and pain. The diversity of additional symptoms reported by patients is consistent with the heterogeneous symptomology of iNHL.